THE POSITIONING OF LATGALE`S LATVIAN IDENTITY IN NEWSPAPERS: „RĒZEKNES VĒSTIS”, „VIETĒJĀ LATGALES AVĪZE”, „LATGALES LAIKS” (2008–2010) - Murinska, Sandra (Via Latgalica, 2012)
One of the most prominent, standardized and popular makers of identity nowadays are the means of mass media. In Latgale region, the dominant mass media type is press: local towns’ and regions’ newspapers, which are easily available and also widely demanded and stable tool of socialization. They own the central role as a source of information, as well as the arena of public discourse and the intermediary for culture and identity.The aim of the article is to determine how the regional newspapers use their influence in the formation of Latgalian Latvian’s identity, what are the types of representation, which express the belonging to Latgale area, inhabitants and values.Using the quantitative content analysis, the frequency of publications and subject categories in the local press (in the period 2008–2010) were determined, in which Latgalian Latvian, Latgalian, Latgalians etc., were mentioned as a participants, as well as some other expressions of belonging. With the qualitative content analysis, the tendencies of building the identification process were determined – the ideas expressed in publications, symbols, themes and attitudes, the characteristics of characters, reflecting the values that are given an important role in the process of Latgalian Latvian’s identity formation in the regional newspapers.Each newspaper relies on its values and events in identity representation. Newspapers „Latgales Laiks” focuses on the activities of Latgale inhabitants in different fields, devoting pages for coverage of sport events and interviews with athletes; important is reflection of Latgalian success in the world. Therefore, in this newspaper, there isa regional identity-building features, coming closer to the work of style of the national newspapers.„Vietējā Latgales Avīze” as a author and interpreters of actual problems choose opinion of representatives of government, education, culture etc. Therefore the newspaper construct Latgalian identity reflecting the success of Latgalians, especially students and young people who are positioned as the talented people of Latgale. It is opposite to newspaper „Rēzeknes Vēstis” strategy – to make Latgalian identity through Catholic values, maintaining thematic pages in Latgalian and reader‘s creative activity. In newspaper „Rēzeknes Vēstis” the reader‘s participation is essentialin positioning identity. It often takes the form as the conflict between past and present, like the historical and political view update inregional and national level.It may be concluded that mainly Latgalian Latvian’s identity is positioned through the reflection of social relations: the mutual relations and the material results, thus mentioning family, work and creative growth as the main values. The most strongly the importance of Latgalian’s identity is revieled and highlighted in the reflection of their life-stories, emotional affection to patrimonial values, birthplace, reflecting past events, and which is defined as the basis for further development of Latgale.